On Giving Guidance to the CPA Candidate. - Stettler, Howard F. (The Accounting Review, 1978)
CPA examination performance of two groups of candidates is analyzed, providing a basis for counseling students as to factors related to success in passing the CPA examination. Of key importance is the indication that a failing candidate who continues to retake the examination is likely to experience marked variation in examination scores on successive attempts as well as some improvement. Personal factors influencing success on the examination are also analyzed.